Emotional experiences of Indonesian health science students with self-harm: a phenomenological study - Meidiana Dwidiyanti; Geovanny Serviam Permana Putri Rahamitu; Luky Dwiantoro; Nur Setiawati Dewi; Sri Padma Sari; Alifia Dian Yusriana (International Journal of Public Health Science (IJPHS), 2026)
Health students often face academic pressure and interpersonal conflicts that can affect their emotional regulation, thereby increasing the risk of self-harm behavior. This study aimed to explore the emotional experiences of health students who have engaged in self-harm through a phenomenological approach. A total of 8 participants (aged 18-25 years) who had engaged in self-harm and came from various health study programs participated in in-depth interviews lasting 45-70 minutes. The results of the study reveal three main themes: i) psychosocial stress as a trigger for negative emotions, ii) the role of social support in the recovery process, and iii) coping mechanisms and the need for professional intervention. These findings reveal emotional dynamics that have not been widely explored in the context of health students in Indonesia, particularly how self-harm is perceived as a strategy to control excessive emotional intensity. This study makes a new contribution by highlighting the need for interventions based on emotional regulation and increased social support that are appropriate to the subjective experiences of health students. Interventions based on empathy and psychological approaches that are more sensitive to the cultural context of the campus are the main recommendations.